2017
DOI: 10.1038/s41556-017-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

A homeostatic apical microtubule network shortens cells for epithelial folding via a basal polarity shift

Abstract: Epithelial folding is typically driven by localized actomyosin contractility. However, it remains unclear how epithelia deform when myosin levels are low and uniform. In the Drosophila gastrula, dorsal fold formation occurs despite a lack of localized myosin changes, while the fold-initiating cells reduce cell height following basal shifts of polarity via an unknown mechanism. We show that cell shortening depends on an apical microtubule network organized by the CAMSAP protein Patronin. Prior to gastrulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 46 publications
9
101
0
Order By: Relevance
“…These are only two of the examples where our findings are likely to hold true. There are multiple other instances, whereupon maturing and differentiating epithelial cells develop an apical microtubule meshwork, including cells of mammalian airways, and even cells in culture [16,56,57]. Furthermore, the same rules are likely to apply to squamous cells, where despite having specialized apical microtubules, the cells' depth is so small, that microtubules are constrained within a thin plane similar to that in our experimental model [58,59].…”
Section: Our System Is a Particular But Generalizable Scenariomentioning
confidence: 55%
“…These are only two of the examples where our findings are likely to hold true. There are multiple other instances, whereupon maturing and differentiating epithelial cells develop an apical microtubule meshwork, including cells of mammalian airways, and even cells in culture [16,56,57]. Furthermore, the same rules are likely to apply to squamous cells, where despite having specialized apical microtubules, the cells' depth is so small, that microtubules are constrained within a thin plane similar to that in our experimental model [58,59].…”
Section: Our System Is a Particular But Generalizable Scenariomentioning
confidence: 55%
“…1 C). During 105 mid-late cellularization, Patronin::GFP shifted to a more apical localization at cell 106 junctions in both the mesoderm and ectoderm ( another study at this developmental stage (Takeda et al, 2018). During gastrulation, 108 medioapical Patronin::GFP foci localized to the center of medioapical myosin patches 109 ( Fig.…”
Section: And C; 92mentioning
confidence: 86%
“…While the regulation and organization of actomyosin during apical constriction 53 has been well-studied, the organization of the microtubule cytoskeleton and its 54 importance is less well understood. In epithelia, there is evidence for different 55 microtubule functions, such as regulating assembly or position of the adherens junctions 56 (Harris and Peifer, 2005;Stehbens et al, 2006;Meng et al, 2008;Le Droguen et al, 57 2015), recruiting apical myosin (Booth et al, 2014), regulating RhoA (Rogers et al, 58 2004;Nagae et al, 2013), and providing a counter-force resisting actomyosin 59 contraction (Takeda et al, 2018;Singh et al, 2018). Importantly, studies have shown 60 that microtubules are necessary for cell shape changes, like apical constriction (Lee and 61 Harland, 2007;Booth et al, 2014).…”
Section: Introduction 17mentioning
confidence: 99%
“…Patronin/CAMSAP proteins have emerged recently as key MT regulators at ncMTOCs, though their exact functional mechanisms remain elusive (Goodwin and Vale, 2010;Wang et al, 2015b;Khanal et al, 2016;Nashchekin et al, 2016;Muroyama and Lechler, 2017;Sanchez and Feldman, 2017;Wu and Akhmanova, 2017;Martin and Akhmanova, 2018;Takeda et al, 2018;Tillery et al, 2018). Patronin protects and stablizes MT minus ends by antagonizing Kinesin-13…”
Section: A New Paradigm For Mt Assembly At Mtocsmentioning
confidence: 99%